2021
DOI: 10.4102/sajip.v47i0.1834
|View full text |Cite
|
Sign up to set email alerts
|

Stress, flourishing and intention to leave of teachers: Does coping type matter?

Abstract: Orientation: Teachers face a demanding work environment which might cause stress. Depending on teachers’ coping profile, distress might indirectly affect teachers’ intentions to resign from their jobs via their flourishing.Research purpose: This study aimed to investigate the associations between teachers’ perceived stress, flourishing at work, intention to leave their jobs and coping types.Motivation for the study: The effect of stress on flourishing at work has not been studied in relation to teachers’ inten… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0
2

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 67 publications
0
7
0
2
Order By: Relevance
“…In this study, the researcher aimed to find out the development of teacher well-being (i.e., burnout) and some of the consequences. It turned out that teacher self-efficacy, as a personal outcome for teachers, was negatively affected Marais- Opperman et al (2021) Researchers operationalized flourishing as emotional, psychological, and well-being. The well-being statuses were negatively related with teachers' intentions to leave, a personal outcome for teachers Teaching Practice Seo & Yuh (2021) Researchers observed that teacher stress affected teacher-student interactions, as part of the teaching practices.…”
Section: Discussionmentioning
confidence: 99%
“…In this study, the researcher aimed to find out the development of teacher well-being (i.e., burnout) and some of the consequences. It turned out that teacher self-efficacy, as a personal outcome for teachers, was negatively affected Marais- Opperman et al (2021) Researchers operationalized flourishing as emotional, psychological, and well-being. The well-being statuses were negatively related with teachers' intentions to leave, a personal outcome for teachers Teaching Practice Seo & Yuh (2021) Researchers observed that teacher stress affected teacher-student interactions, as part of the teaching practices.…”
Section: Discussionmentioning
confidence: 99%
“…According to Marais-Opperman et al ( 2021), the demanding work environment which teachers face on day-to-day basis has often compelled some to resign their jobs. This is common where teachers fail to cope with the distress (Marais-Opperman et al, 2021). It becomes difficult for education authorities to retain in the service teachers whose well-being have been compromised and disrupted (Marais-Opperman et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…This is common where teachers fail to cope with the distress (Marais-Opperman et al, 2021). It becomes difficult for education authorities to retain in the service teachers whose well-being have been compromised and disrupted (Marais-Opperman et al, 2021).…”
Section: Literature Reviewmentioning
confidence: 99%
“…Some of these situations lead to creative and innovative solutions while others result in negative outcomes such as exhaustion, so positive and negative stress must be differentiated. Whereas positive stress may help teachers to flourish at work, negative stress -distress -leads to burnout and creates anxiety, disengagement, and the desire to leave one's job (Marais-Opperman et al, 2021;Susanty, 2017). Negative stress harms faculty members, impacts relationships with families and friends, and affects student learning.…”
Section: Catching Stressmentioning
confidence: 99%